2015
DOI: 10.1002/hbm.22893
|View full text |Cite
|
Sign up to set email alerts
|

Brain stimulation improves cognitive control by modulating medial‐frontal activity and preSMA‐vmPFC functional connectivity

Abstract: Previous research has demonstrated that brain stimulation can improve inhibitory control. However, the neural mechanisms underlying such artificially induced improvement remain unclear. In this study, by coupling anodal transcranial direct current stimulation (atDCS) with functional MRI, we found that atDCS over preSMA effectively improved stopping speed, which was associated with increased BOLD response in the preSMA and ventromedial prefrontal cortex (vmPFC). Furthermore, such atDCS-induced BOLD increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 55 publications
5
55
1
Order By: Relevance
“…The vmPFC is the primary cortical target of limbic projections (54), and stress-induced increases in activity may provide top-down modulation of amygdala reactivity and negative emotions. While not typically associated with inhibitory control, augmented vmPFC activity during reactive inhibition has been reported following methylphenidate administration (55) and neuromodulation of the pre-SMA (56). These findings, together with our observations following acute stress, could implicate norepinephrine signaling in altered vmPFC activation, but further research is needed.…”
Section: Discussionsupporting
confidence: 55%
“…The vmPFC is the primary cortical target of limbic projections (54), and stress-induced increases in activity may provide top-down modulation of amygdala reactivity and negative emotions. While not typically associated with inhibitory control, augmented vmPFC activity during reactive inhibition has been reported following methylphenidate administration (55) and neuromodulation of the pre-SMA (56). These findings, together with our observations following acute stress, could implicate norepinephrine signaling in altered vmPFC activation, but further research is needed.…”
Section: Discussionsupporting
confidence: 55%
“…Lesion of the dmPFC in humans led to deficits in control in the presence of response conflicts (Nachev et al 2007). Direct current stimulation of the pre-supplementary motor area (pre-SMA) facilitated response inhibition (Yu et al 2015). The pCC is part of the default mode network (DMN).…”
Section: Discussionmentioning
confidence: 99%
“…We did not however, observe a stimulation-induced effect on SSRTs, inhibition accuracy and signal-respond RTs. While two recent studies found polarity-specific effects on SSRTs after anodal stimulation over pre-SMA (Liang et al, 2014;Yu et al, 2015), the lack of SSRTs and signal-respond RTs are in line with the findings from recent studies by Hsu and colleagues (2011) and . The authors applied anodal and cathodal tDCS over the SMFC to investigate its functional role in response inhibition operations.…”
Section: Discussionsupporting
confidence: 90%
“…tDCS is a non-invasive brain stimulation method that can be employed to modulate cortical activity and establish a causal role of specific regions or functionally/anatomically connected networks in behaviour (Liang et al, 2014;Yu, Tseng, Hung, Wu, & Juan, 2015). In addition, it can shed light on the systems-level neural mechanisms of specific cognitive operations by influencing performance in a polarityspecific manner (Filmer, Dux, & Mattingley, 2014).…”
Section: Discussionmentioning
confidence: 99%